The Effect Of Islamic Financial Inclusion And Human Development Index On Poverty Rate In Indonesia - Vanesa, Ulva (ITB AAS INDONESIA Surakarta, 2024)
Poverty is a problem that always exists in various countries around the world including Indonesia, where Indonesia is included in the 100 poorest countries in the world. From Nurkse's theory, the solution that can be done to reduce poverty is to increase financial inclusion and human development index. Islamic financial inclusion in Indonesia is still very low and the human development index in Indonesia continues to increase but the poverty rate in Indonesia is still high. Therefore, the main problem identification in this research is the effect of Islamic financial inclusion and human development index on poverty in Indonesia. This research uses quantitative methods and uses secondary data obtained from the Central Bureau of Statistics website, and the Financial Services Authority. This research uses panel data regression analysis which takes data from 33 provinces in Indonesia from 2018 to 2022. The results of this study indicate that Islamic financial inclusion and the human development index have a negative and significant effect on the poverty rate in Indonesia. For this reason, it is necessary for government regulations to continue to increase Islamic financial inclusion and the human development index so that poverty in Indonesia can continue to decrease.